Improving the Efficacy of Tumor Radiosensitization Through Combined Molecular Targeting - Hintelmann, Katharina; Kriegs, Malte; Rothkamm, Kai; Rieckmann, Thorsten (Frontiers in Oncology, 2020)
Chemoradiation, either alone or in combination with surgery or induction chemotherapy, is the current standard of care for most locally advanced solid tumors. Though chemoradiation is usually performed at the maximum tolerated doses of both chemotherapy and radiation, current cure rates are not satisfactory for many tumor entities, since tumor heterogeneity and plasticity result in chemo- and radioresistance. Advances in the understanding of tumor biology, a rapidly growing number of molecular targeting agents and novel technologies enabling the in-depth characterization of individual tumors, have fuelled the hope of entering an era of precision oncology, where each tumor will be treated according to its individual characteristics and weaknesses. At present though, molecular targeting approaches in combination with radiotherapy or chemoradiation have not yet proven to be beneficial over standard chemoradiation treatment in the clinical setting. A promising approach to improve efficacy is the combined usage of two targeting agents in order to inhibit backup pathways or achieve a more complete pathway inhibition. Here we review preclinical attempts to utilize such dual targeting strategies for future tumor radiosensitization.